1995
DOI: 10.1530/eje.0.1320229
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor (EGF)- and transforming growth factor alpha-stimulated invasion and growth of follicular thyroid cancer cells can be blocked by antagonism to the EGF receptor and tyrosine kinase in vitro

Abstract: We have shown recently that epidermal growth factor (EGF) enhanced invasion and growth of differentiated thyroid cancer cells in vitro and in vivo. The present study analyzed the effects of transforming growth factor alpha (TGF-alpha) on invasion and growth of a follicular thyroid cancer cell line (FTC133) and whether blocking the EGF receptor by a monoclonal antibody (Mab528) or blocking the tyrosine kinase of the receptor by genistein abolished the EGF- and TFG-alpha-mediated effects. Growth and invasion (pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…Our present results closely agree with our previous work (41) and other studies (42) reporting that EGFR is overexpressed in differentiated and anaplastic thyroid carcinomas and that targeting EGFR by anti-EGFR antibodies (EGFR antibody 528) completely neutralized the EGF-mediated stimulation of FTC cell growth and invasion in culture (19). Furthermore, our findings agree with studies showing that genistein, a general tyrosine kinase antagonist, can abrogate growth stimulation of EGF and transforming growth factor-a (TGF-a) on invasion and growth of FTC cells (19).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our present results closely agree with our previous work (41) and other studies (42) reporting that EGFR is overexpressed in differentiated and anaplastic thyroid carcinomas and that targeting EGFR by anti-EGFR antibodies (EGFR antibody 528) completely neutralized the EGF-mediated stimulation of FTC cell growth and invasion in culture (19). Furthermore, our findings agree with studies showing that genistein, a general tyrosine kinase antagonist, can abrogate growth stimulation of EGF and transforming growth factor-a (TGF-a) on invasion and growth of FTC cells (19).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our findings agree with studies showing that genistein, a general tyrosine kinase antagonist, can abrogate growth stimulation of EGF and transforming growth factor-a (TGF-a) on invasion and growth of FTC cells (19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our observations also have significant implications for the spread of epithelial tumors that commonly express ␣v␤5 (53). In this regard, it is particularly interesting that the autocrine production of TGF-␣ has been linked to both the expression of malignancy and motility in carcinomas (54). While the precise mechanism of uPA⅐uPAR in cell migration is not completely understood, it appears that this ligand-receptor complex functionally cooperates with integrin ␣v␤5 to promote the migration of carcinoma cells.…”
Section: Figmentioning
confidence: 70%
“…46 The v-erbA oncogene coding for a truncated thyroid hormone receptor has been shown to cooperate with platelet-derived growth factor to increase in vitro invasion. 47 In other cell types a role for the EGFR has also been demonstrated; for example, Hölting et al 48 showed that in a follicular thyroid cancer cell line EGF or TGF-␣ stimulated invasion over unstimulated cells (p Ͻ 0.02). Similar results were found by Hamada et al 49 in rat mammary carcinoma cells in which EGF stimulated in vitro invasion in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%